Effect of Alcohol Disinfection on the Handle and Blade of Meat and Fish Knives by using ATP Inspection and Microbial Stamp Test (Global Journal of Medical Research, 2020)
It is valid to show the cooks a visual hygiene test result to prevent food poisoning. Therefore, in this study, for hygiene control of the handle and blade of frequently used kitchen knives, we report inspections using the ATP wiping test and microbial stamp test. The results of the ATP wiping test showed that the ATP value decreased statistically significantly after washing compared to after cooking, and after70% alcohol spraying compared to after washing. A microbial stamp test (general bacteria, Escherichia coli, staphylococcous aureus, Salmonella, Vibrio parahaemolyticus) was also performed at the same time as the ATP test. As a result, the number of bacteria did not change much or decreased even after washing or spraying with 70% alcohol. In particular, Escherichia coli, staphylococcou aureus were found to be difficult to decrease even after 70%alcohol sprayings. In the future, it will be necessary to consider increasing the number of alcohol sprays of hygiene management using sodium hypochlorite.
Keywords: ATP test; microbial stamp test; the handle of the knife; the blade of the knife; alcohol disinfection